Hubungan antara FoMO (Fear of Missing Out) dengan Kepuasan Hidup pada Mahasiswa Kota Padang - Dani, Tri Ahmad; Kurniawan, Rizal (Lembaga Yasin AlSys, 2024)
Students who are in the transition from adolescence to early adulthood (18-25 years) need to have high life satisfaction. High life satisfaction provides benefits such as forming positive self-esteem, encouraging academic achievement, to providing better career opportunities because high life satisfaction encourages better performance and productivity in students. Low life satisfaction encourages individuals to access social media as an effort to seek pleasure and satisfaction in life, however inappropriate and excessive use of social media can have an impact in the form of FoMO (Fear Of Missing Out). This study aims to determine whether there is a relationship between FoMO and life satisfaction in Padang city students. The research design used was quantitative correlational with the population involving all students in the city of Padang. Data collection was conducted through an online questionnaire using the FoMO scale and the Likert scale of life satisfaction. Data analysis used the Spearman Correlation technique, and the results showed a negative relationship between FoMO and life satisfaction in Padang city students, with a correlation value (r) of -0.166 and a significance value (p) of 0.002.